PERAN PONDOK PESANTREN DALAM PENGEMBANGAN SIKAP ENTREPRENEUR SANTRI DI PESANTREN MIFTAHUL ULUM PALABUHANRATU - Acip; Wina Elvalina (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2022)
The role of Islamic boarding schools is very important in the life of Indonesian society, especially Islamic society. The essence of Islamic boarding school education is to prepare generations of people to live their best lives before Allah as Khalifah on earth in carrying out their duties. This study aims to get an in-depth description of the role of Islamic boarding schools in developing students' entrepreneurial attitudes at Miftahul Ulum Islamic boarding schools. Theoretical and empirical activities in this study are classified under the qualitative phenomenological method, because researchers report the results of research on the concept of Islamic religious education in developing students' entrepreneurial attitudes, then describe and integrate the concept with existing theories. The results of the study show that planning and implementation are carried out in the form of a strategy to improve academic quality through integrated curriculum and the formation of integrity, character and personality through the development of Islamic values. The methods provided, such as Go To Your Post, Lecture Method, Drill Method and Demonstration Method, must be carried out in a systematic and measurable manner so that they are in accordance with what was previously planned.